1976
DOI: 10.1093/ajcn/29.10.1073
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance during recovery from malnutrition

Abstract: This report presents an account of energy balance of young Jamaican children recovering from protein-energy malnutrition (PEM). This was done in three steps. Initially the true gross energy of a formula used in the treatment of PEM was determined by bomb calorimetry. Then its metabolizable energy content was determined in a group of nine children recovering from PEM. In a similar but different group of eight children total daily metabolizable energy intake (EI), average rate of weight gain (g/kg/day) (WG), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 25 publications
6
79
2
2
Order By: Relevance
“…The positive energy balance necessary to deposit 6 kg of body weight over 4 y can be calculated to be a sustained 30-40 kcal/day excess. [24][25][26] Proviso these calculations are of limited value, since they are nondynamic and do not take into account the fact that the measured positive energy balance is likely to be attenuated over time by the over-compensatory increase in energy expenditure caused by the weight gain. 43,44 We have previously been unable to show a relationship between cTEI and self-reported energy intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive energy balance necessary to deposit 6 kg of body weight over 4 y can be calculated to be a sustained 30-40 kcal/day excess. [24][25][26] Proviso these calculations are of limited value, since they are nondynamic and do not take into account the fact that the measured positive energy balance is likely to be attenuated over time by the over-compensatory increase in energy expenditure caused by the weight gain. 43,44 We have previously been unable to show a relationship between cTEI and self-reported energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…8 cTEI, as estimated in this study, depended on accurate measurements of body weight and rested on many metabolic assumptions. [24][25][26] For example, the calculations of the caloric equivalent of changes in body energy stores during the week-long measurement must be interpreted with caution, since we do not have any experimental evidence that all subjects gained or lost the same amount of water and metabolically active tissue. We believe that rigorous validation studies are needed to establish how closely cTEI approximates the true daily energy intake in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] The energy equivalence of fat mass (FM) and fat-free mass (FFM) loss was determined from standard caloric equivalents: 9.45 kcal per g FM and 1.13 kcal per g FFM. 31,32 Five different approaches were employed to determine the predicted weight loss:…”
Section: Calculations Of Energy Requirements and Energy Deficitmentioning
confidence: 99%
“…Micro-organisms tend to colonize the intestinal tract in PEM and are a potential source of endotoxin production and gram-negative sepsis. It has been suggested that administration of Metronidazole (for anaerobic organisms) and Colistin (for aerobic organisms) reduces the risk of infection and facilitates the regmeration of an intact intestinal mucosa (Suskind, 1975). During the past 18 months, mortality at our Unit in Jamaica has fallen to zero and one of the new measures introduced has been the prophylactic administration of Metronidazole to children who are severely ill. We cannot say whether the association is causal or merely coincidental, but it would appear to merit investigation.…”
Section: Vol 38mentioning
confidence: 99%